Conservative Nonsurgical Approach for Management of a Case of Type II Dens in Dente - Navin S. Agarwal; Shishir Singh; Padmini Chandrasekhar; Gaurav Kulkarni; Rajesh Podar (Case Reports in Dentistry)
Dens in dente is a developmental dental anomaly which poses a challenge for the endodontist due to its complex pulpal anatomy. In this case report, a class 2 dens in dente was managed nonsurgically. A 32-year-old female reported with a palatal swelling and pain in the upper front region of the jaw. On examination, #7 was observed to be malformed and showed a negative pulpal sensibility test. Radiographic and CBCT analysis revealed Ohler’s type 2 dens in dente with a periapical radiolucency. In the first visit, invagination was removed using diamond-coated ultrasonic tips, the canal was minimally instrumented, and premixed calcium hydroxide was injected in the canal which accidentally extruded periapically. After two weeks, a draining sinus was observed on the palatal side which when traced, lead to #7. Intracanal dressing was replaced with a mix of powdered calcium hydroxide and saline. The dressing was replaced every two weeks, and radiographs were taken, which revealed the resorption of extruded calcium hydroxide and reduction in the osseous defect. Biodentine was used to obturate the entire canal space. Subsequent follow-up radiographs till 24 months showed significant periapical healing and resorption of extruded calcium hydroxide.